D-meson production in p-Pb collisions at √sNN=5.02 TeV and in pp collisions at √s=7 TeV - Adam, Jaroslav; Angelov, Venelin; Danisch, Meike; Deisting, Alexander; Fleck, Martin; Glässel, Peter; Klewin, Sebastian; Knichel, Michael Linus; Leardini, Lucia; Mercado Pérez, Jorge; Oyama, Ken; Pachmayer, Yvonne C.; et al. (Physical review, 2016)
Background: In the context of the investigation of the quark gluon plasma produced in heavy-ion collisions, hadrons containing heavy (charm or beauty) quarks play a special role for the characterization of the hot and dense medium created in the interaction. The measurement of the production of charm and beauty hadrons in proton-proton collisions, besides providing the necessary reference for the studies in heavy-ion reactions, constitutes an important test of perturbative quantum chromodynamics (pQCD) calculations. Heavy-flavor production in proton-nucleus collisions is sensitive to the various effects related to the presence of nuclei in the colliding system, commonly denoted cold-nuclear-matter effects. Most of these effects are expected to modify open-charm production at low transverse momenta (pT) and, so far, no measurement of D-meson production down to zero transverse momentum was available at mid-rapidity at the energies attained at the CERN Large Hadron Collider (LHC).
*The ALICE Collaboration: J. Adam, V. Anguelov, M.C. Danisch, A. Deisting, M.G. Fleck, P. Glaessel, S. Klewin, M.L. Knichel, L. Leardini, J. Mercado Perez, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, J. Stachel, J. Stiller, M.A. Voelkl, D.F. Weiser, J. Wilkinson, B. Windelband, M. Winn, A. Zimmermann [und 977 weitere Personen]
Im Titel stehen der Ausdruck "sNN" und der Buchstabe s unter dem Wurzelsymbol
Gesehen am 21.07.2020